2015
DOI: 10.4103/0975-7406.155972
|View full text |Cite
|
Sign up to set email alerts
|

Gnathological splint therapy in temporomandibular joint disorder

Abstract: Temporomandibular joint (TMJ) forms an integral functional part of stomatognathic system. Position, shape, structure and function of teeth have an influence on the proper functioning and health of TMJ. But a problem associated with TMJ is often neglected, and treatment for it is mostly restricted to palliative therapy. A proper understanding of the underlying cause of temporomandibular joint disorder (TMD) is necessary to device a proper treatment plan. Etiology of TMDs varies from idiopathic reasons to system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…Víctor Pardo Juárez ósea subcondral, cuerpos óseos libres y pseudoquistes. El conocimiento de estos cambios óseos es fundamental para el diagnóstico correcto de las disfunciones asociadas con la enfermedad y para la adecuada planificación del tratamiento ( [48][49][50][51][52][53][54][55][56][57][58][59][60] ).…”
Section: Discussionunclassified
“…Víctor Pardo Juárez ósea subcondral, cuerpos óseos libres y pseudoquistes. El conocimiento de estos cambios óseos es fundamental para el diagnóstico correcto de las disfunciones asociadas con la enfermedad y para la adecuada planificación del tratamiento ( [48][49][50][51][52][53][54][55][56][57][58][59][60] ).…”
Section: Discussionunclassified
“…13 Ahora bien, después de haber disertado las similitudes en cuanto a los protocolos de atención y resultados de la investigación realizada con la citada en los antecedentes, ahora discutiremos acerca de los artículos o investigaciones con las que no coincidimos, como lo es la investigación efectuada por Gnanashanmugham y col. en el país de la india en el año 2015 en el cual el paciente al utilizar la férula durante 8 meses refiere una disminución del dolor en la región de la ATM, reducción de la frecuencia de los episodios del dolor de cabeza y la rigidez en el cuello, la sensibilidad sobre los músculos de la masticación desaparecieron del mismo modo que las desviación a la apertura de la mandíbula, lo que difiere a nuestro estudio. 14 Dentro de los antecedentes encontramos otros usos que se le pueden dar a las férulas oclusales como pueden ser tratamiento en fracturas condilares en pacientes infantiles, elevación de la temperatura y tonicidad de los músculos de la masticación, rehabilitación en pacientes con una dimensión vertical disminuida por desgaste dental, pacientes con luxación anterior del disco con reducción, pacientes sometidos a cirugía ortognatica; de igual modo en la literatura revisada en los antecedentes encontramos artículos o investigaciones que comparaban la eficacia en la férula oclusal total rígida con otros dispositivos como son las férulas de tope anterior y las férulas blandas, donde no se observaron diferencias significativas en cuanto a la eficiencia y eficacia.…”
Section: Materials Y Métodosunclassified
“…The etiology of TMD is multifactorial and includes the presence of dental malocclusions, parafunctional habits, facial trauma, and psychological disorders. In most patients, more than one factor is present (Gnanashanmugham et al 2015). In patients with chronic pain, it has been observed that the presence of the psychological-social factor such as stress-anxiety, influences the control of the facial neuromusculature and the mandibular posture, being considered the main trigger or aggravating factor of the TMD(Cabrera et al 2009).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…This condylar displacement brings continuous effects and periods of parafunctional muscle activity(Puigdollers and Iglesia 2005), such as the contraction of the sarcomere group of muscle fibers, the increase in blood vessel pressure, decrease in blood and oxygen volume, and the production of lactic acid, causing the pain and sensitivity of the chewing muscles to any muscular contraction during occlusion. Likewise, the specific use of gnathological splints has been reported successfully in the literature (Gnanashanmugham et al 2015;Rivero 2000;Lotzmann 1996), with an effectiveness of up to 90% in the relaxation of the masticatory muscles and the control of myofascial pain, allowing a temporary correction of the occlusal component of the TMD without irreversibly altering the position of the teeth. The gnathological splint aims to achieve a musculoskeletal stable position, by simulating an ideal occlusion free of occlusal interferences in which the teeth present a uniform and simultaneous contact, thus allowing the relaxation and reduction of muscle tension.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%